TOWARDS A NEW ACCOUNT OF HERMENEUTICS: GENEALOGY VERSUS HERMENEUTICS. - Bielskis, Andrius (Problems / Problemos, 2008)
The essay analyses the difference between Hans-Georg Gadamer's and Alasdair MacIntyre's conceptions of hermeneutic philosophy, on the one hand, and Nietzschean genealogy, on the other. It argues that Ricoeur's famous distinction between 'hermeneutics of faith' and 'hermeneutics of suspicion' in the light of the ontological reading of Nietzsche's genealogy is misleading. Rather than trying to understand Nietzsche's philosophy as the hermeneutics of suspicion, it is more accurate to see Nietzsche's and Foucault's interpretive philosophy in terms of genealogy. The contrast between Gadamerian hermeneutics and Nietzschean genealogy, the one hand, as well as reading Gadamer hermeneutics in the light of MacIntyre's conception of tradition-constituted and tradition-constitutive philosophical inquiry, on the other, allow us to formulate an alternative conception of hermeneutics. The essay argues that hermeneutics is inevitably linked to tradition: hermeneutics depend on and draws its moral and intellectual resources from tradition as well as determines and continues tradition further.